The Effect of Using Madrasati Platform on Developing Digital Culture Skills among English Language Teachers in Jazan Region - Al-Hazmi, Iman Mohammad Mohammad; Mowkaly, Khaled Hussein (Journal of Curriculum and Teaching Methodology, 2022)
The aim of the research is to identify the impact of using the Madrasati platform in developing the digital culture skills of English language teachers in the Jazan region, and its relationship to gender and years of experience, and using the research descriptive survey method; The study sample consisted of (194) male and female English language teachers in the Sabya Education Department in Jazan region. A questionnaire consisting of (33) phrases was applied to them, distributed over three areas: information culture skills, media culture skills, and information and communication technologies culture skills; The study found that the Madrasati platform has a very big role in developing the digital culture skills of English language teachers, at a rate of (87.6%), and the field of ICT culture skills ranked first with a percentage of (91.4) and a very large impact level, followed by the field of ICT culture skills. Information culture skills, with a percentage (87.4%), with a very large level of impact, while the field of media culture skills ranked third with a percentage (84.2%), with a very large level of influence, and the results showed that there were no statistically significant differences in the use of the platform My school in developing digital culture skills for English language teachers in the Jazan region is attributed to the gender variable or to the variable years of experience. The research recommended the necessity of including digital culture skills in the English language teacher preparation program in the faculties of education, and teachers’ employment of modern technologies in teaching English.